2000
DOI: 10.1074/jbc.m004724200
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Amino Acid Sequence Crucial for Heparin Binding to Collagen V

Abstract: Collagen V is a minor component of connective tissues that plays a fundamental role in matrix organization. Indeed, direct evidence was obtained from collagen V gene mutations that provoke obvious alteration of fibril aggregates (1-4). Aside from its role in collagen fibril formation, collagen V interacts specifically with a variety of macromolecules in the extracellular matrix (5) and with several cell-surface receptors such as integrins (6, 7), tyrosine kinase receptors (8, 9), and proteoglycans (10, 11). Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 30 publications
1
27
2
Order By: Relevance
“…This may in part result from the indistinct requirements for "consensus" heparin binding motifs of proteins. Clusters of six to eight alternating basic amino acid residues have been shown to be the requisite factors for recognition of sulfated polysaccharides (2,20).…”
Section: Discussionmentioning
confidence: 99%
“…This may in part result from the indistinct requirements for "consensus" heparin binding motifs of proteins. Clusters of six to eight alternating basic amino acid residues have been shown to be the requisite factors for recognition of sulfated polysaccharides (2,20).…”
Section: Discussionmentioning
confidence: 99%
“…KGHRG in ␣1(I) and KGIRGH in ␣2(I)) (28), whereas in collagens ␣1(V) 3 and ␣1(XI)␣2(XI)␣1(II) basic residues are spread throughout the sequence (i.e. KXGPRGXRGPTGPRGXR present in ␣1(V), ␣1(XI), and ␣2(XI) chains) (29). In ColQ, our results showed that the most important residues for heparin interaction are concentrated in the sequence GRPGBBGB, differing from those found in collagens.…”
Section: Heparin-binding Capacity Of Colq Resides Exclusively In the mentioning
confidence: 99%
“…Those experiments were carried out using the monomeric, non-triple-helical fragment HepV, and full-length, triple-helical isoforms of collagen V, namely the (␣1(V)) 2 ␣2 heterotrimer and the (␣1(V)) 3 homotrimer. The dependence of the interaction between collagen V and heparin/heparan sulfate upon the triple-helical conformation of collagen V was also investigated with a triple-helical synthetic peptide containing the 15 amino acid residues of the previously defined heparin binding site (10). Taken altogether, these results emphasize differences between the binding of the HepV fragment and of the full-length collagen V molecules to heparan sulfate.…”
mentioning
confidence: 70%
“…The recombinant production of HepV in Escherichia coli has set the stage for identifying the heparin binding site by site-directed mutagenesis and affinity chromatography. We have previously identified within the Lys 905 -Arg 921 sequence of the ␣1(V) chain five basic residues participating in the binding of HepV to heparin (10), but the molecular features of heparin responsible for the specific recognition of HepV have not been characterized, although the characteristics of heparin/heparan sulfate-protein interactions have been elucidated for several other proteins (for reviews, see Refs. 11 and 12).…”
mentioning
confidence: 99%
See 1 more Smart Citation